Electronic structure, magnetic, optical and transport properties of half-Heusler alloys RhFeZ(Z = P, As, Sb, Sn, Si, Ge, Ga, In, Al) – a DFT study. (3rd August 2021) - Meenakshi, R.; Aram Senthil Srinivasan, R.; Amudhavalli, A.; Rajeswarapalanichamy, R.; Iyakutti, K.
ABSTRACT: The properties such as structural, mechanical, electronic structure, magnetic, optical and transport properties of the half-Heusler alloys of Rhodium RhFeZ(Z = P, As, Sb, Sn, Si, Ge, Ga, In, Al) are investigated at normal pressure. The alloys RhFeSb, RhFeSn, RhFeGe, RhFeGa, RhFeIn and RhFeAl are more stable in γ -phase. But the alloys RhFeP, RhFeAs and RhFeSi exhibit stability in β -phase under normal pressure. Among the investigated alloys, RhFeSn and RhFeGe are half-metallic at normal pressure. All the other half-Heusler alloys, RhFeP, RhFeAs, RhFeSb, RhFeSi, RhFeGa, RhFeIn and RhFeAl are ferromagnetic at normal pressure. To understand the transport properties, Seebeck coefficients, electrical conductivity, thermal conductivity and power factor are examined. The investigation infers that the alloys RhFeSn and RhFeGe possess remarkable transport properties and find potential applications in thermoelectric devices.